Question
upstudy study bank question image url

(39.5. а) \( \left\{\begin{array}{l}x-3 y=5, \\ 3 x+2 y=4 ;\end{array}\right. \) б) \( \left\{\begin{array}{l}3 x+y=1, \\ 2 x-5 y=-22\end{array}\right. \) ०39.6. а) \( \left\{\begin{array}{l}x+y=4 \\ 4 x-5 y=7\end{array}\right. \) б) \( \left\{\begin{array}{l}x-y=6, \\ 5 x-2 y=-3\end{array}\right. \) ०39.7. а) \( \left\{\begin{array}{l}40 x+3 y=-10 \\ 20 x-7 y=-5\end{array}\right. \) б) \( \left\{\begin{array}{l}5 x+2 y=1, \\ 15 x+3 y=3\end{array}\right. \) о39.8. а) \( \left\{\begin{array}{l}3 x+7 y=46 \\ 4 x-3 y=12\end{array}\right. \) б) \( \left\{\begin{array}{l}-3 x+4 y=24 \\ 5 x+3 y=-40\end{array}\right. \)

Ask by Burton Haynes. in Turkey
Nov 24,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

а) \(x = 2, y = -1\) б) \(x = -1, y = 4\) а) \(x = 3, y = 1\) б) \(x = -5, y = -11\) а) \(x = -\frac{1}{4}, y = 0\) б) \(x = \frac{1}{5}, y = 0\) а) \(x = 6, y = 4\) б) \(x = -8, y = 0\)

Solution

Давайте решим каждую из систем уравнений по порядку. ### 39.5 а) \[ \begin{cases} x - 3y = 5 \quad (1) \\ 3x + 2y = 4 \quad (2) \end{cases} \] Решим систему методом подстановки. Из уравнения (1) выразим \(x\): \[ x = 3y + 5 \] Подставим это значение в уравнение (2): \[ 3(3y + 5) + 2y = 4 \\ 9y + 15 + 2y = 4 \\ 11y + 15 = 4 \\ 11y = 4 - 15 \\ 11y = -11 \\ y = -1 \] Теперь подставим \(y\) обратно в (1): \[ x - 3(-1) = 5 \\ x + 3 = 5 \\ x = 2 \] Ответ: \(x = 2, y = -1\). б) \[ \begin{cases} 3x + y = 1 \quad (1) \\ 2x - 5y = -22 \quad (2) \end{cases} \] Из уравнения (1) выразим \(y\): \[ y = 1 - 3x \] Подставим это значение в уравнение (2): \[ 2x - 5(1 - 3x) = -22 \\ 2x - 5 + 15x = -22 \\ 17x - 5 = -22 \\ 17x = -22 + 5 \\ 17x = -17 \\ x = -1 \] Теперь подставим \(x\) обратно в (1): \[ 3(-1) + y = 1 \\ -3 + y = 1 \\ y = 4 \] Ответ: \(x = -1, y = 4\). ### 39.6 а) \[ \begin{cases} x + y = 4 \quad (1) \\ 4x - 5y = 7 \quad (2) \end{cases} \] Из уравнения (1) выразим \(y\): \[ y = 4 - x \] Подставим это значение в уравнение (2): \[ 4x - 5(4 - x) = 7 \\ 4x - 20 + 5x = 7 \\ 9x - 20 = 7 \\ 9x = 27 \\ x = 3 \] Теперь подставим \(x\) обратно в (1): \[ 3 + y = 4 \\ y = 1 \] Ответ: \(x = 3, y = 1\). б) \[ \begin{cases} x - y = 6 \quad (1) \\ 5x - 2y = -3 \quad (2) \end{cases} \] Из уравнения (1) выразим \(x\): \[ x = y + 6 \] Подставим это значение в уравнение (2): \[ 5(y + 6) - 2y = -3 \\ 5y + 30 - 2y = -3 \\ 3y + 30 = -3 \\ 3y = -3 - 30 \\ 3y = -33 \\ y = -11 \] Теперь подставим \(y\) обратно в (1): \[ x - (-11) = 6 \\ x + 11 = 6 \\ x = 6 - 11 \\ x = -5 \] Ответ: \(x = -5, y = -11\). ### 39.7 а) \[ \begin{cases} 40x + 3y = -10 \quad (1) \\ 20x - 7y = -5 \quad (2) \end{cases} \] Умножим (1) на 7 и (2) на 3, чтобы избавиться от \(y\): \[ \begin{cases} 280x + 21y = -70 \quad (3) \\ 60x - 21y = -15 \quad (4) \end{cases} \] Сложим (3) и (4): \[ 280x + 21y + 60x - 21y = -70 - 15 \\ 340x = -85 \\ x = -\frac{85}{340} = -\frac{1}{4} \] Теперь подставим \(x\) обратно в (1): \[ 40(-\frac{1}{4}) + 3y = -10 \\ -10 + 3y = -10 \\ 3y = 0 \\ y = 0 \] Ответ: \(x = -\frac{1}{4}, y = 0\). б) \[ \begin{cases} 5x + 2y = 1 \quad (1) \\ 15x + 3y = 3 \quad (2) \end{cases} \] Умножим (1) на 3: \[ 15x + 6y = 3 \quad (3) \] Теперь вычтем (2) из (3): \[ (15x + 6y) - (15x + 3y) = 3 - 3 \\ 3y = 0 \\ y = 0 \] Теперь подставим \(y\) обратно в (1): \[ 5x + 2(0) = 1 \\ 5x = 1 \\ x = \frac{1}{5} \] Ответ: \(x = \frac{1}{5}, y = 0\). ### 39.8 а) \[ \begin{cases} 3x + 7y = 46 \quad (1) \\ 4x - 3y = 12 \quad (2) \end{cases} \] Умножим (1) на 3 и (2) на 7: \[ \begin{cases} 9x + 21y = 138 \quad (3) \\ 28x - 21y = 84 \quad (4) \end{cases} \] Сложим (3) и (4): \[ 9x + 21y + 28x - 21y = 138 + 84 \\ 37x = 222 \\ x = \frac{222}{37} = 6 \] Теперь подставим \(x\) обратно в (1): \[ 3(6) + 7y = 46 \\ 18 + 7y = 46 \\ 7y = 28 \\ y = 4 \] Ответ: \(x = 6, y = 4\). б) \[ \begin{cases} -3x + 4y = 24 \quad (1) \\ 5x + 3y = -40 \quad (2) \end{cases} \] Умножим (1) на 5 и (2) на 3: \[ \begin{cases} -15x + 20y = 120 \quad (3) \\ 15x + 9y = -120 \quad (4) \end{cases} \] Сложим (3) и (4): \[ -15x + 20y + 15x + 9y = 120 - 120 \\ 29y = 0 \\ y = 0 \] Теперь подставим \(y\) обратно в (1): \[ -3x + 4(0) = 24 \\ -3x = 24 \\ x = -8 \] Ответ: \(x = -8, y = 0\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Did you know that systems of linear equations have been around for centuries? Around 2000 years ago, the ancient Chinese solved linear equations, using methods that laid the groundwork for algebra as we know it. Their text, "The Nine Chapters on the Mathematical Art," includes problems that closely resemble what we're solving today. So next time you tackle these problems, think of yourself as part of a long tradition of mathematicians! In real life, these equations are everywhere! Engineers use them to determine loads and forces, while economists rely on them to model supply and demand. You might be surprised to learn that even in simple budgeting or planning short trips, systems of equations can help balance out resources or time. So, remember, next time you're juggling multiple tasks, think of your equations as a helpful guide for a balanced life!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy